Impacto das condi??es de sa?de bucal na qualidade de vida de gestantes de alto risco - Barreto, Catarine Boaventura Bastos (2023)
Pregnancy is a physiological phenomenon that involves several changes in physical, social and emotional aspects. The state of a pregnant woman's oral health is related to her general health and in high-risk pregnancies, the oral health condition, in addition to being impacted by the physiological changes during the pregnancy period, is also influenced by pre-existing systemic diseases, interfering with quality of these women's lives. The objective of this work was to evaluate the effect of oral health conditions and levels of stress and anxiety on the quality of life of high-risk pregnant women. This work had as products a scientific article for publication, an informative booklet and a folder to be distributed to SUS professionals and patients. A cross-sectional study was carried out, with a quantitative approach. Pregnant women attending the high-risk Prenatal Program of the Unified Health System of Alagoinhas-BA participated in this research. Data collection occurred through interviews using the Oral Health Impact Profile (OHIP-14), the Dental Anxiety Scale (DAS), the Perceived Stress Scale (PSS-14) and a structured questionnaire consisting of sociodemographic, clinical and obstetrics. After the interview, the pregnant women underwent a complete periodontal examination and were classified according to the presence and severity of periodontitis. The DMFT index was used to assess the presence of caries. The average DMFT found was 9.54, [?6.65], in relation to periodontal condition, 29.2% were diagnosed with gingivitis, the occurrence of periodontitis among pregnant women was 65.8% according to the criterion of Page and Eke, 2007, and according to the criterion Gomes-filho et al. modified, 2018 the occurrence was 13.3%, in relation to the psychosocial dimensions studied, 60.8% presented a low state of anxiety regarding dental treatment, perceived stress presented an average value of 27.2 [?12] and the OHIP-14 an average of 13.3 [?11]. The correlations between the total OHIP14 score and periodontal condition and between the OHIP14 and the variables relating to the oral health condition of pregnant women did not show statistical significance. The results demonstrated an association between the total OHIP14 score and dental anxiety, and a statistically significant correlation was also observed between the OHIP14 and levels of perceived stress. In view of the results obtained, it was concluded that the oral health condition did not have a significant impact on the Quality of Life Related to Oral Health (OHRQOL), however, the levels of perceived stress and dental anxiety impacted the OHRQoL of high-risk pregnant women. In this way, the importance of outlining and continually evaluating the sociodemographic, psychosocial and oral health profile of high-risk pregnant women was observed for planning care actions and developing strategies aimed at offering comprehensive care to this population.